(untitled) (Biological Sciences - PJSIR, 2001)
The basicringsystem8H-pyrano[3,2-flquinoxalineanditsalkyl,arylandoxoderivatives (5a-5d)werepreparedby the reaction of 5,6-diaminocoumarin with appropriate 1,2-dicarbonylcompounds.